Peran Hemaglutinin dan Hemolisin pada Escherichia coli Sorbitol-negatif Isolat Burung Puyuh pada Proses Infeksi Secara in Vitro - Khusnan Khusnan; Wahyu Prihtiyantoro; Dwi Kusmanto (Jurnal Sain Veteriner, 2021)
Abstract Escherichia coli sorbitol-negative in quails cause economic loss due to the death, growth rate inhibition, decreased egg production, and increased medical treatment. Escherichia coli sorbitol-negative has many virulence factors, including hemagglutinin and hemolysin. The aim of this study is to determine the role of hemagglutinin and hemolysin in the infection process of Escherichia coli sorbitol-negative in vitro. This study was performed using 23 isolates of Escherichia coli sorbitol-negative from quails, 52.2% (12 of 23 isolates) had hemagglutinin, while 34.8% (8 out of 23 isolates) had hemolysin. Isolates with hemagglutinin were more attached to human buccal epithelial cells than isolates without hemagglutinin (P <0.05). Isolates with hemolysin were less phagocyted by macrophages compared to isolates which without hemolysin (P <0.05). Escherichia coli sorbitol-negative isolates from quails that have hemagglutinin and hemolysin are pathogenic isolates that possess the potential to cause colibasilosis and transmission between quails and other birds.